Wound healing and regeneration in the reef building coral Acropora millepora - Xu, Jane; Mead, Oliver; Moya, Aurelie; Caglar, Cüneyt; Miller, David J.; Adamski, Marcin; Adamska, Maja (Frontiers in Ecology and Evolution, 2023)
Branching scleractinian corals are niche-constructing organisms, providing continuously- growing, structural foundation for spectacularly biodiverse coral reef ecosystems. A large part of their success lies in the ability to quickly regenerate following mechanical damage. Even now, when the corals undergo great decline due to anthropogenic weather and storm extremes, it is surprising how little is known about molecular mechanisms governing regeneration in these iconic organisms. In this study, we used RNA-seq to identify genes involved in the regeneration of Acropora millepora, starting with the initial wound closure up to complete rebuilding of lost structures. Many of the differentially expressed genes we found in the wound healing steps are homologues of genes known to be involved in wound healing and regeneration of bilaterian and other cnidarian species, prominently including multiple components of FGF and Wnt signalling pathways. Comparison between genes involved in wound healing and continuous growth of the colony demonstrates both similarity and distinctiveness of the genetic programs controlling these processes. A striking example is specific expression of c-Fos, a transcription factor with conserved role in early injury response, during the earliest stages of wound healing of A. millepora. By comparing results obtained in diverse experimental conditions including a closed-loop, recirculating aquarium and a flow-through system of marine station, we have demonstrated feasibility of using zooxanthellate scleractinian corals as experimental models in fundamental biology research, including studies of regeneration.